Steppe Eagles in Bokey-Orda Nature Reserve and Ashiozek Sanctuary (Western Kazakhstan Region) in 2022–2023 - Ilya E. Smelyansky; Andrei A. Tomilenko; Anna N. Barashkova; Roman N. Aleksandrovich; Beibars Kitibaev; Alyona Koshkina (Пернатые хищники и их охрана)
The Steppe Eagle (Aquila nipalensis) is a typical and representative inhabitant of the steppe, a key predator in steppe ecosystems, and until recently the most common and abundant of Kazakhstan’s large raptors. In the last two decades, its abundance and range here have been greatly reduced. The species’ nesting group in the Volga-Ural interfluve has been little studied in the last 15 years. The Bokey-Orda State Nature Reserve (SNR) and the Ashiozek Zoological Sanctuary were established in the western part of Western Kazakhstan Oblast in 2022. Together, they encompass the almost completely endorheic basin of the Ashiozek River along with its tributary water bodies – a complex of the salt lakes Aralsor, Batpak, Zhalpak, and Araltobe and a number of smaller such lakes. This vast (6,570 km2 ) territory contains desertified and dry steppes and northern halophyte and hemihalophyte deserts. The main objective for establishing these protected areas is to protect the saiga population and that ungulate’s habitats. The steppe eagle is also recognized as a priority conservation target. Additionally, the IBA “Lower reaches of the Ashchyozek River” is located within this region, an area identified on the basis of its importance for the Steppe Eagle.